Floating macro-litter pollution in the northern South China Sea. (1st January 2023) - Liu, Mingming; Lin, Mingli; Huang, Xiaoyu; Yang, Zixin; Caruso, Francesco; Baini, Matteo; Bocconcelli, Alessandro; Rosso, Massimiliano; Li, Songhai
Abstract: Marine litter pollution, particularly plastics pollution, is an increasing global concern. While various studies have contributed useful information on this topic, there has been a scarcity of data on floating marine macro-litter (FMML) in poorly monitored areas such as the South China Sea (SCS). This paper describes a large-scale FMML assessment research in the northern SCS. Our data indicated the ubiquitous presence, abundant quantity, spatiotemporal variability, complex composition, and potential sources of FMML in the investigated region during boreal spring-summer periods over multiple years. According to observer-based records, the average FMML density was estimated to be 131.0 ± 91.8 items/km 2 (mean ± SD), with anthropogenic FMML density of 118.7 ± 86.2 items/km 2 . Anthropogenic and natural items accounted for 90.6% and 5.5% of the total, respectively. Plastics (72.0%) and styrofoam (9.3%) dominated the recorded items. The great majority of items (92.1%) were characterized by small size of ≤20 cm. Labels of plastic bottle/packaging litter indicated that identifiable sources included surrounding countries of the SCS. Fishing activities were recognized as key sources of FMML, with 15.3% of FMML items likely being fishing-related. Globally, known estimates of FMML densities could vary from 0.002 to 578 items/km 2, with plastics accounting for 34.8–99.0%. Therefore, marine pollution from anthropogenic FMML in our investigated area ranked at a medium-to-high level around the globe. To conclude, this study demonstrated that the SCS is one of the world's hotspot areas with FMML pollution and sheds light on marine litter pollution, especially plastics pollution, in this intensively human-exploited but poorly monitored region. In future research, FMML pollution in other sections of SCS and possible negative impacts of FMML on marine ecosystems and megafauna should be further examined. Graphical abstract: Image 1 Highlights: Anthropogenic FMML density in the northern SCS: 118.7 ± 86.2 items/km 2 (mean ± SD). Plastics (72.0%) and styrofoam (9.3%) dominated the total FMML. Most FMML items (92.1%) were characterized by small size (≤20 cm). FMML pollution in the nrothern SCS ranks a medium-to-high level worldwide.